2003
DOI: 10.1016/s1097-2765(03)00490-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NF-κB Signaling by Pin1-Dependent Prolyl Isomerization and Ubiquitin-Mediated Proteolysis of p65/RelA

Abstract: The transcription factor NF-kappaB is activated by the degradation of its inhibitor IkappaBalpha, resulting in its nuclear translocation. However, the mechanism by which nuclear NF-kappaB is subsequently regulated is not clear. Here we demonstrate that NF-kappaB function is regulated by Pin1-mediated prolyl isomerization and ubiquitin-mediated proteolysis of its p65/RelA subunit. Upon cytokine treatment, Pin1 binds to the pThr254-Pro motif in p65 and inhibits p65 binding to IkappaBalpha, resulting in increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
616
5
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(652 citation statements)
references
References 42 publications
18
616
5
5
Order By: Relevance
“…Ryo et al (2003) showed that Pin1 expression in human breast cancer samples correlates with nuclear levels of RelA. This study suggests that Pin1 binds to RelA, inhibiting interaction with IkB and resulting in increased nuclear accumulation of this NF-kB subunit (Figure 2).…”
Section: Activation Downstream Of Growth Factors and Growth Factor Rementioning
confidence: 84%
“…Ryo et al (2003) showed that Pin1 expression in human breast cancer samples correlates with nuclear levels of RelA. This study suggests that Pin1 binds to RelA, inhibiting interaction with IkB and resulting in increased nuclear accumulation of this NF-kB subunit (Figure 2).…”
Section: Activation Downstream Of Growth Factors and Growth Factor Rementioning
confidence: 84%
“…It remains to be determined whether differences in experimental conditions account for these different observations. In contrast to factors that antagonize NF-kB's transcriptional and protective activities, the peptidyl prolyl-isomerase Pin1 enhances nuclear accumulation of RelA by blocking its association with IkBa and by interfering with suppressor of cytokine signalling 1 (SOCS-1)-dependent ubiquitination and degradation of RelA (Ryo et al, 2003). Although direct evidence is still lacking about whether Pin1 enhances the protective activity of NF-kB, Pin1 is frequently upregulated in breast cancer and in mouse mammary tumors (Ryo et al, 2003;Currier et al, 2005).…”
Section: Mechanisms Implicated In Nf-kb's Proapoptotic Activitymentioning
confidence: 99%
“…In contrast to factors that antagonize NF-kB's transcriptional and protective activities, the peptidyl prolyl-isomerase Pin1 enhances nuclear accumulation of RelA by blocking its association with IkBa and by interfering with suppressor of cytokine signalling 1 (SOCS-1)-dependent ubiquitination and degradation of RelA (Ryo et al, 2003). Although direct evidence is still lacking about whether Pin1 enhances the protective activity of NF-kB, Pin1 is frequently upregulated in breast cancer and in mouse mammary tumors (Ryo et al, 2003;Currier et al, 2005). A recently published report indicates that the intracellular domain of Notch (Notch-IC) interacts with NF-kB to compete with IkBa, consequently enhancing NF-kB's nuclear retention and sustained NF-kB activity (Shin et al, 2006).…”
Section: Mechanisms Implicated In Nf-kb's Proapoptotic Activitymentioning
confidence: 99%
“…Moreover, the interaction of Pin1 and phosphorylated p65/RelA subunit of NFκB prevents NFκB from binding to IκB that increases its transcriptional activity and consequentially elevate the cyclin D1 level (36). Besides upregulation of the cyclin D1 gene expression, Pin1 has been demonstrated to directly bind to pT286-Pro motif of cyclin D1 and resulted in increasing its protein stability (37).…”
Section: Discussionmentioning
confidence: 99%